2003
DOI: 10.1542/peds.111.1.140
|View full text |Cite
|
Sign up to set email alerts
|

A Smoking Cessation Intervention for Parents of Children Who Are Hospitalized for Respiratory Illness: The Stop Tobacco Outreach Program

Abstract: This study demonstrates the feasibility of engaging parents in smoking cessation interventions at the time of child hospitalization for respiratory illness. Previous work done in a similar sample of parental smokers has shown extremely low ever-use rates of cessation programs. High rates of acceptance of in-hospital and telephone counseling in this study support the notion of child hospitalization as a teachable moment to address parental smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
174
3
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(182 citation statements)
references
References 35 publications
(33 reference statements)
4
174
3
1
Order By: Relevance
“…Other studies, focusing on parents of older children admitted to the hospital with asthma, have shown that illness provides a "teachable moment." 1,3,12 However in our study, the parents of sicker infants were less likely to accept referral. Perhaps the danger of secondhand smoke to premature lungs is less apparent or compelling to parents than the danger of smoking to an asthmatic.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Other studies, focusing on parents of older children admitted to the hospital with asthma, have shown that illness provides a "teachable moment." 1,3,12 However in our study, the parents of sicker infants were less likely to accept referral. Perhaps the danger of secondhand smoke to premature lungs is less apparent or compelling to parents than the danger of smoking to an asthmatic.…”
Section: Discussioncontrasting
confidence: 65%
“…[1][2][3] Although several studies have evaluated smoking cessation in parents of newborns, fewer have evaluated smoking cessation efforts targeting parents of newborns specifically in the postpartum hospital stay. In the Newborns Excel Without Secondhand Smoke (NEWS) study, Winickoff et al found that parents in the postpartum period were receptive to enrolling in tobacco cessation services and may be more motivated to quit at that time.…”
mentioning
confidence: 99%
“…Questions used in this study to assess tobacco control service delivery were used previously in our other inpatient or outpatient studies. 16,22 Covariates collected included gender, age, race, education, smoking history, smoking behavior inside the home and car, and attitudes about the dangers of child' s TSE.…”
Section: Methodsmentioning
confidence: 99%
“…11,16,21,22,[29][30][31][32] The intervention includes (1) routine screening for parental tobacco use using a CEASE Action Sheet, which helped the office staff identify each smoking family member and document smoking status in the child' s medical record; (2) motivational messaging that is based on the parents' own concerns as well as potential teachable moments that may be cued by the child' s illness; and (3) recommendation and possible provision of nicotine patch and gum by the clinician, and enrollment in the free state quitline. The intervention is designed to function within existing systems of care; research staff deliver none of the clinical tobacco dependence treatment.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation